How pore formation in complex biological membranes is governed by lipid composition, mechanics, and lateral sorting - Starke, Leonhard J; Allolio, Christoph; Hub, Jochen S (PNAS nexus, 2025)
The primary function of biological membranes is to enable compartmentalization among cells and organelles. Loss of integrity by the formation of membrane pores would trigger uncontrolled depolarization or influx of toxic compounds, posing a fatal threat to living cells. How the lipid complexity of biological membranes enables mechanical stability against pore formation while, simultaneously, allowing for ongoing membrane remodeling is largely enigmatic. We performed molecular dynamics simulations of eight complex lipid membranes including the plasma membrane and membranes of the organelles endoplasmic reticulum, Golgi, lysosome, and mitochondrion. To quantify the mechanical stability of these membranes, we computed the free energy of transmembrane pore nucleation as well as the line tension of the rim of open pores. Our simulations reveal that complex biological membranes are remarkably stable, however, with the plasma membrane standing out as exceptionally stable, which aligns with its crucial role as a protective layer. We observe that sterol content is a key regulator for biomembrane stability, and that lateral sorting among lipid mixtures influences the energetics of membrane pores. A comparison of 25 model membranes with varying sterol content, tail length, tail saturation, and head group type shows that the pore nucleation free energy is mostly associated with the lipid tilt modulus, whereas the line tension along the pore rim is determined by the lipid intrinsic curvature. Together, our study provides an atomistic and energetic view on the role of lipid complexity in biomembrane stability.
Keywords: lipid membranes; molecular dynamics simulations; pore formation; Helfrich theory